Clinical meaningfulness and psychometric robustness of the MG Symptoms PRO scales in clinical trials in adults with myasthenia gravis - Regnault, Antoine; Habib, Ali A.; Creel, Kristin; Kaminski, Henry J.; Morel, Thomas (Frontiers in Neurology, 2024)
Objectives The objective of this research was to generate psychometric evidence supporting the myasthenia gravis (MG) symptoms patient-reported outcome (PRO) scales as a fit-for-purpose measure of severity of core symptoms of MG and provide information allowing their meaningful interpretation using data from a phase 3 study in MG. Methods Data from the MycarinG study, a phase 3 study of rozanolixizumab in patients with generalized MG who experience moderate to severe symptoms (ClinicalTrials.gov Identifier: NCT03971422) were analyzed with both classical test theory (CTT) and Rasch measurement theory (RMT). Meaningful within-individual change and group-level meaningful change were estimated for three MG Symptoms PRO scales using anchor- and distribution-based methods. Anchor-based methods used patient global impression of severity (PGIS) and change (PGIC) in MG symptoms as anchors. Results Good measurement properties of the MG Symptoms PRO scales were shown in the sample of 200 participants: good to excellent reliability (test–retest and internal consistency reliability) and validity (associations between items and scores within the MG Symptoms PRO scales and between the MG Symptoms PRO scores and other clinical outcomes—MG ADL, QMG score, MGC score, and MGFA classes—were as expected); and the items showed good coverage of the continuum and fit to the Rasch model. Triangulation of the anchor- and distribution-based method results led to the definition of clinically meaningful within-patient improvement in scores for Muscle Weakness Fatigability (−16.67), Physical Fatigue (−20.00), and Bulbar Muscle Weakness (−20.00), with associated ranges. Benchmarks are also proposed for the interpretation of group-level results. Conclusion The strong psychometric performance of the MG Symptoms PRO scales and the information generated to guide its interpretation supports its use in clinical trials for demonstrating the clinical benefits of new treatments targeting core symptoms of MG (muscle weakness fatigability, physical fatigue, bulbar muscle weakness, respiratory muscle weakness, and ocular muscle weakness).